Neutrophil extracellular traps activate lung fibroblast to induce polymyositis‐related interstitial lung diseases via TLR9‐miR‐7‐Smad2 pathway. Issue 2 (10th December 2019) - Zhang, Sigong; Jia, Xueqin; Zhang, Qiuyue; Zhang, Li; Yang, Jing; Hu, Caihong; Shi, Junnian; Jiang, Xiao; Lu, Jinyue; Shen, Haili
Abstract: Excessive neutrophil extracellular trap (NET) formation may contribute to polymyositis (PM)‐associated interstitial lung diseases (ILD), but the underlying mechanism is not fully revealed. In this study, we found that NET accelerated the progression of ILD and promoted pulmonary fibrosis (PF) in vivo. miR‐7 expression was down‐regulated in lung tissue of PM group than control group, and NETs further decreased miR‐7 expression. TLR9 and Smad2 were up‐regulated in lung tissue of PM group than control group, and NETs further increased TLR9 and Smad2 expressions. In vitro experiments showed that PMA‐treated NETs accelerated the proliferation of LF and their differentiation into myofibroblast (MF), whereas DNase I decreased the promotion effect of NETs. Neutrophil extracellular trap components myeloperoxidase (MPO) and histone 3 also promoted the proliferation and differentiation of LF. In addition, we demonstrated that TLR9 involved in the regulation of NETs on LF proliferation and differentiation, and confirmed the interaction between miR‐7 and Smad2 in LF. Finally, miR‐7‐Smad2 pathway was confirmed to be involved in the regulation of TLR9 on LF proliferation and differentiation. Therefore, NETs promote PM‐related ILD, and TLR9‐miR‐7‐Smad2 signalling pathway is involved in the proliferation of LFs and their differentiation into MFs.